The oxidative cost of helping and its minimization in a cooperative breeder. (21st February 2022) - Covas, Rita; Lardy, Sophie; Silva, Liliana R; Rey, Benjamin; Ferreira, André C; Theron, Franck; Tognetti, Arnaud; Faivre, Bruno; Doutrelant, Claire
Abstract: Cooperative actions are beneficial to the group, but presumably costly to the individual co-operators. In cooperatively breeding species, helping to raise young is thought to involve important energetic costs, which could lead to elevated exposure to reactive oxygen species, resulting in oxidative stress. However, identifying such costs can be difficult if individuals adjust their investment in helping in relation to environmental conditions or their own physiological condition. Experimental approaches are therefore required to quantify the costs of helping but, to date, these have been infrequent. Here, we combined correlational and experimental data to investigate the oxidative cost of helping-at-the-nest and how this affects helping decisions in wild sociable weavers Philetairus socius, a colonial cooperatively breeding bird. At the correlational level, we found that the probability of helping was influenced by the interaction of an individual's oxidative state and age: compared to younger birds, older individuals were more likely to help when they had higher oxidative damage, and the opposite trend was found for younger individuals. After experimentally increasing the energetic cost of flight, manipulated helpers in breeding colonies decreased nestling feeding rates and incurred an increase in oxidative damage, which was not present in manipulated helpers in non-breeding colonies. This indicates that individuals decreased their helping behavior to minimize the associated costs. These results suggest that oxidative stress can influence helping decisions and underlie a trade-off between cooperation and self-maintenance, which is central to understanding when helping might take place in this and other species. Abstract : We found that helping decisions in wild sociable weavers are influenced by the individuals' physiological condition, age and cost of flight, and that individuals decreased their helping behaviour to minimise the associated costs. These results suggest a trade-off between cooperation and self-maintenance, which is important to understand when helping might take place in this and other species.